Corneal Cap Thickness and Its Effect on Visual Acuity and Corneal Biomechanics in Eyes Undergoing Small Incision Lenticule Extraction - Ting Liu; Ting Yu; Lina Liu; Kaijian Chen; Ji Bai (Journal of Ophthalmology)
Purpose. To evaluate the effect of corneal cap thickness on visual acuity and corneal biomechanics in small incision lenticule extraction (SMILE) for the treatment of myopia. Methods. Forty eyes of 20 patients undergoing SMILE for the treatment of myopia were enrolled in this prospective controlled study. The patients with 510 μm–560 μm central corneal thickness (CCT) and a refractive spherical equivalent of −3.00 D to −8.00 D were included. It was designed randomly to undergo SMILE with a 110 μm cap thickness in one eye and 150 μm cap thickness in the other. Ophthalmic examinations included best-corrected and uncorrected visual acuity (UCVA); refractive status, contrast sensitivity, and objective visual quality were evaluated at 2 h, 4 h, and 24 h postoperatively; while at 3 months after the procedure, corrected intraocular pressure (IOP), higher order aberrations (HOAs), and morphologic modifications of corneal architecture of both eyes were assessed. Results. Compared with the 150 μm group, the incidence of OBL was significantly higher in the 110 μm cap thickness group (P=0.004), and UCVA, Strehl ratio (SR), objective scatter index (OSI), modulation transfer function (MTF) cutoff frequency, and photopic and scotopic contrast sensitivity at medium spatial frequency were all significantly better in 110 μm group at 2 h and 24 h postoperatively (P<0.05). Corneal spherical aberration and corrected IOP by Corvis ST were significantly higher in the 110 μm group at 3 months postoperatively (P<0.05). No statistically significant differences were found in manifest refraction, UCVA, SR, OSI, MTF cutoff, and mesopic and photopic contrast sensitivity at low frequency, photopic contrast sensitivity at high frequency, endothelial density, corneal coma, and total HOAs at 3 months after the procedure. No visual decline was found in the patients in this study. Conclusions. Both 110 μm and 150 μm cap thickness in SMILE were safe and effective for treatment of myopia. A 110 μm cap thickness demonstrated better visual outcomes during early and late postoperative periods with higher corneal spherical aberration and corrected IOP at 3 months postoperatively. This trial is registered with ChiCTR-IOR-17013369.